Transformational Leadership: A Bibliometric Analysis of Core Themes and Influential Studies - Loso Judijanto; Ivon Arisanti (West Science Business and Management, 2026)
This study aims to map the intellectual structure, core themes, and emerging trends in transformational leadership research through a bibliometric approach. Data were collected from the Scopus database, covering a specified publication period, and analyzed using VOSviewer to examine co-occurrence, co-citation, and collaboration patterns. The results reveal that transformational leadership remains a central and highly influential topic, strongly associated with organizational performance, job satisfaction, and employee behavior. The network analysis identifies several major thematic clusters, including organizational outcomes, psychological dimensions, and knowledge and innovation management. Overlay visualization indicates a temporal shift toward emerging themes such as ethical leadership, emotional intelligence, and sustainable development, reflecting the evolving relevance of transformational leadership in addressing contemporary organizational challenges. Meanwhile, density analysis highlights a well-established research core alongside underexplored areas that offer opportunities for future studies. This study contributes by providing a comprehensive mapping of the transformational leadership research landscape and offers insights into potential directions for advancing the field.